Genomic surveillance and serological profile of SARS-CoV-2 variants circulating in Macaé and nearby cities, southeastern Brazil - da Silva, Amanda Cristina Veiga Fernandes; Silva, Carina Azevedo Oliveira; de Sousa, Graziele Fonseca; Coelho, Viktoria Aparecida Gomes Silva; da Cunha, Lucas Tavares; Paes, Artur Nunes; Pozzobon, Allan Pierre Bonetti; das Graças dos Santos, Daniele; Carpes, Raphael Mello; Costa, Evenilton Pessoa; Monteiro-de-Barros, Cintia; Nepomuceno-Silva, José Luciano; et al. (Frontiers in Microbiology, 2024)
Introduction: A characteristic of the COVID-19 pandemic has been the sequential emergence and global dissemination of SARS-CoV-2 variants, noted for their enhanced transmission efficiency. These variants with mutations in the Spike glycoprotein (S-glycoprotein), which interacts with ACE2 receptors in human cells is critical for infection, affects the transmissibility of the virus, which is a matter of great concern for public health. Objective: This research analyses the effects these variants on a cohort of vaccinated and naturally infected individuals from the cities of Macaé-RJ, Rio das Ostras-RJ, and Campos dos Goytacazes-RJ, Brazil, from March 2021 to March 2023. Methods: This investigation encompasses the Alpha (B.1.1.7), Gamma (P.1), Delta (B.1.617.2, B.1.671.3), and Omicron (BQ.1, BQ.1.1 sublines, and BF.7) variants, focusing on their genomic surveillance and implications for the disease’s epidemiology. The experimental analysis included a control group (vaccinated and uninfected subjects), and an infected group (post-vaccinated subjects). Samples from nasopharyngeal swabs underwent viral detection via RT-qPCR for diagnosis confirmation. RNase H-dependent RT-qPCR (rhAmp-PCR) and third-generation sequencing were used to detect SARS-CoV-2 variants. Anti-S-glycoprotein immunoglobulins were also evaluated for vaccinated infected and noninfected volunteers. Symptoms from infected individuals were compiled in order to reveal patterns of clinical signs associated with viral infection. Results: The study included 289 participants, with infections identified by Gamma (n = 44), Delta (n = 189), and Omicron (n = 56) variants. The prevalent symptoms among the naturally infected participants were cough, fever, sore throat, headache, and runny nose. For Omicron, cognitive symptoms such as memory loss and concentration issues were reported. Interestingly, the infected vaccinated group had higher anti-S-glycoprotein IgM production (n = 28, 0.2833 ± 0.09768 OD) compared to the uninfected vaccinated group (n = 14, 0.1035 ± 0.03625 OD). Conversely, anti-S-glycoprotein IgG production was higher in the control group (n = 12, 1.770 ± 0.1393 OD) than in the infected vaccinated group (n = 26, 1.391 ± 0.1563 OD). Conclusion: This comprehensive study enables monitoring of predominant variants and their correlation with clinical cases, providing valuable insights for public health. Our research group continues to survey circulating variants, contributing to the global understanding of the pandemic.